Change leadership at local self-government in the context of COVID-19: The case study of Lithuanian municipal administration - Vineta Račaitė-Samušienė; Diana Šaparnienė; Vita Jukneviciene (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Contemporary challenges require public sector institutions to adapt the changing environment and to ensure an appropriate internal management processes, including the leadership. Leaders are expected to inspire and create a vision, and advocate for that vision throughout the periods of growth, disruption or uncertainty. In recent years of pandemic the importance of change leadership increases in local self-government. The aim of this article is to examine the change leadership in Lithuanian municipal administration in the context of the COVID-19 pandemic and on the basis of research results to form the assumptions of strengthening of change leadership in local self-government organisations. Analysis of theoretical aspects revealed main features of change leadership and its connection with transformational leadership in the context of public administration institutions focusing on the COVID-19 pandemic. The scientific methods such as document analysis and qualitative semi-structured interview have been used for the empirical research, based on the case study of selected Lithuanian municipal administration as the field of research. The research results revealed that during the period of changes assumed by the COVID-19 pandemic the managers of Lithuanian municipal administration act like leaders of change, resolving problems in teams and flexibly reacting to current issues.
Keywords: O15; J45; H12; 330; Change leadership; Transformational leadership; Local self-government; Public sector; Municipal administration; COVID-19; Lithuania